ANALYSIS OF ADAPTATION OF TRADITIONAL MARKET TRADERS IN THE DIGITAL EVOLUTION (CASE STUDY OF PETISAH MARKET CLOTHING SHOP) - Nasution, Arfiany Sepyanty Putri; Amelia, Cahya; Kaban, Fadhila Putri; Andani, Nadzhira Putri; Fazira, Sri Mutia (PERSPEKTIF: Journal of Social and Library Science, 2024)
Traditional markets that used to be the center of buying and selling activities are now facing major changes due to the emergence of digital markets. Because the presence of e-commerce platforms and social media offers convenience for consumers and sellers, such as wider accessibility, fast transactions, and efficient payment systems. Changes in digital marketing methods are also felt by clothing sellers in one of the traditional markets in Medan City, namely Petisah Market. This research method is qualitative with the research subjects in this study being market players who make transactions at the Petisah market. This study uses data collection techniques such as interviews and observations. Based on the results of an interview with one of the shop owners in the Petisah market, it was revealed that the problems experienced by Petisah market traders were such as high price levels which caused a lack of consumer interest in shopping. Several shops in Petisah tax also market online stores on the Shopee application via Instagram to attract the attention of online shopping enthusiasts with the potential for friendly service, friendly service is an important potential possessed by traditional markets in order to excel over modern markets and e-commerce. The main recommendation to ensure the success of Petisah Market traders' adaptation in facing digitalization is to combine conventional and digital methods